Potential of Lipid Core Peptide Technology as a Novel Self-Adjuvanting Vaccine Delivery System for Multiple Different Synthetic Peptide Immunogens - Olive, Colleen (American Society for Microbiology, 2003)
This study demonstrates the effectiveness of a novel self-adjuvanting vaccine delivery system for multiple different synthetic peptide immunogens by use of lipid core peptide (LCP) technology. An LCP formulation incorporating two different protective epitopes of the surface antiphagocytic M protein of group A streptococci (GAS)—the causative agents of rheumatic fever and subsequent rheumatic heart disease—was tested in a murine parenteral immunization and GAS challenge model. Mice were immunized with the LCP-GAS formulation, which contains an M protein amino-terminal type-specific peptide sequence (8830) in combination with a conserved non-host-cross-reactive carboxy-terminal C-region peptide sequence (J8) of the M protein. Our data demonstrated immunogenicity of the LCP-8830-J8 formulation in B10.BR mice when coadministered in complete Freund's adjuvant and in the absence of a conventional adjuvant. In both cases, immunization led to induction of high-titer GAS peptide-specific serum immunoglobulin G antibody responses and induction of highly opsonic antibodies that did not cross-react with human heart tissue proteins. Moreover, mice were completely protected from GAS infection when immunized with LCP-8830-J8 in the presence or absence of a conventional adjuvant. Mice were not protected, however, following immunization with an LCP formulation containing a control peptide from a Schistosoma sp. These data support the potential of LCP technology in the development of novel self-adjuvanting multi-antigen component vaccines and point to the potential application of this system in the development of human vaccines against infectious diseases.